الاقطاع الإقطاع العسكري في العراق في العصور العباسية المتأخرة(555-656ه/1160-1258م): The military feudalism in Iraq during the Later Abbasid Period.” (555-656 A.H/ 1160- 1258 A.D) - Shawawreh , Fathy; A. M. Al-Jaloudi, Elian (Arts and Social Sciences Series, 2026)
Abstract: Most studies on the economic life in Iraq during the late Abbasid period conclude that the military feudalism implemented then was an extension of the military feudalism known in Iraq during the Buyid and Seljuk periods. A careful reading of the limited primary sources reveals varied applications during these later periods, some extending from the Seljuk era and others closely tied to the conditions of the caliphate, influenced by contemporary systems in the Levant and northern Iraq. This study aims to uncover developments in military institutions, land ownership, and taxation, particularly focusing on military feudalism during the late Abbasid era (555-656 AH / 1160-1258 AD). Keywords: Abbasid Caliphate, feudalism, Seljuks, money.